A G‐quadruplex‐forming RNA aptamer binds to the MTG8 TAFH domain and dissociates the leukemic AML1‐MTG8 fusion protein from DNA. Issue 21 (11th September 2020) - Fukunaga, Junichi; Nomura, Yusuke; Tanaka, Yoichiro; Torigoe, Hidetaka; Nakamura, Yoshikazu; Sakamoto, Taiichi; Kozu, Tomoko
Abstract : MTG8 ( RUNX1T1 ) is a fusion partner of AML1 (RUNX1) in the leukemic chromosome translocation t(8;21). The AML1‐MTG8 fusion gene encodes a chimeric transcription factor. One of the highly conserved domains of MTG8 is TAFH which possesses homology with human TAF4 [TATA‐box binding protein‐associated factor]. To obtain specific inhibitors of the AML1‐MTG8 fusion protein, we isolated RNA aptamers against the MTG8 TAFH domain using systematic evolution of ligands by exponential enrichment. All TAF aptamers contained guanine‐rich sequences. Analyses of a TAF aptamer by NMR, CD, and mutagenesis revealed that it forms a parallel G‐quadruplex structure in the presence of K + . Furthermore, the aptamer could bind to the AML1‐MTG8 fusion protein and dissociate the AML1‐MTG8/DNA complex, suggesting that it can inhibit the dominant negative effects of AML1‐MTG8 against normal AML1 function and serve as a potential therapeutic agent for leukemia. Abstract :